FLUID ADHERENCE LEVEL AMONG PATIENTS UNDERGOING WITH HEMODIALYSIS - Novita Surya Putri; Titin Sukartini; Ferry Efendy (Alta Dharma Publisher, 2019)
Hemodialysis is commonly provided for three times per week to disposal of analyzed waste and fluid volume in the body. Fluid elimination has a risk for fluid excessive in inter-dialytic. The study aimed to determine the level of fluid restrictions among hemodialysis patients. A descriptive study was applied to describe the level of fluid restriction. Fifteen samples were selected using purposive sampling. The findings explained that more than half of patients have poor adherence to restrict the fluid. Around 46% of patients have fair level adherence on fluid Keywords: Hemodialysis, Interdialytic Weight Gain, Adherence to Fluid Restriction